HUBUNGAN KOORDINASI MATA TANGAN DENGAN KEMAMPUAN SHOOTING BOLA BASKET PADA SISWA SMA NEGERI 2 RAHA - La Ode Muhammad Seisar Ramadhan Ombi; Saifu; Wolter Mongsidi (Journal Olympic (Physical Education, Health and Sport), 2021)
The problem in this research is the low physical component of eye hand coordination owned by SMA Negeri 2 Raha students. The variables in this study consisted of one independent variable (eye hand coordination) and one dependent variable (shooting ability). This study aims to investigate the correlation between eye-hand coordination toward basketball shooting ability on senior high school students at SMAN 2 Raha. All of the students of SMA Negeri 2 Raha. This type of research is correlational.were considered as the population of study with total 544 students, the sample were 33 students drawn from the population by using purposive sampling technique. The test instruments were utilized throughout the study including catching and throwing tennis ball. Moreover, the test of basketball shooting was also used as the test instrument.The data were analyzed using correlation statistic of product moment with significant level at 0.05. The result showed that there was a significant correlation between eye-hand coordination toward basketball shooting ability on senior high school students at SMAN 2 Raha rxy = 0,46 > r table (0.05:33) = 0,344 with coefficient of determination = 0,21 or 21 %, eye-hand coordination contributed to basketball shooting ability on senior high school students at SMAN 2 Raha. Based on the results of this analysis, it can be concluded that there is a significant relationship between eye-hand coordination and basketball shooting skills for students at SMA Negeri 2 Raha. Based on the result, it can be concluded that the better the eye-hand coordination, the better the students’ shooting ability on basketball as it revealed at senior high school students at SMAN 2 Raha